Seen from the Viewpoint of a Fish: Posthumanist Observation in Lucien Castaing-Taylor and Véréna Paravel’s ‘Leviathan’ - Chkhaidze, Irina (Sociologija. Mintis ir veiksmas, 2017)
This article conceptualises Lucien Castaing-Taylor and Véréna Paravel’s experimental documentary Leviathan (2012) using Niklas Luhmann’s observation theory and Cary Wolfe’s writing on posthumanism which, significantly influenced by Luhmann’s attack on anthropocentrism in social theory, questions the importance of human agency for social and psychic systems. Leviathan, I argue, engenders perspectives drawn from visual culture that enable a rethinking of hierarchical humanist ethics based on species membership, contributing to posthumanist critical discourse.Leviathan offers a radically non-anthropocentric take on the topic of industrial fishing, presented via innovative use of camera placements and cinematic points of view. Unpredictable camera movements involving contingent framing and angles generate an open-ended work not tied to the human gaze. Shooting from a caught marine animal’s point of view forces the viewer to assume an unexpected perspective. To analyse this particular perspective, I turn to Luhmann’s theories about an observation not tied to human subjectivity, where the subject of observation is simultaneously an object, and where the external world is equally inaccessible to humans and nonhumans alike. In this schema, present in any observation is a constitutive blindness that can only be seen by another observer, but it is this very blindness which makes the observation possible.
Keywords: visual culture; experimental documentary; second-order systems theory; social theory; posthumanism